Removal of Mercury, Cadmium, and Lead Ions by Penicillium sp. - Sánchez-Castellón, Juan; Urango-Cárdenas, Iván; Enamorado-Montes, Germán; Burgos-Nuñez, Saudith; Marrugo-Negrete, José; Díez, Sergi (Frontiers in Environmental Chemistry, 2022)
Discharge of metals into the environment generates significant impact upon human health and biological cycles. Some microorganisms such as fungi are known for their high metal adsorption capacity. The aim of this work was to evaluate the capacity for Penicillium sp. molds in the removal of Pb, Cd, and Hg from aqueous solutions by isolating the fungal strain from an artisanal gold mine soil. The biosorption experiments shown that optimum conditions for metals removal were noted at 150 min, acidic pH (4-5), 60 °C and 2 g of biomass. The accomplished removal was 92.4% for Pb, 80% for Cd, and 99.6% of Hg, at a concentration of 51.5 mg/L. Kinetic analyses and isotherms fit best the pseudo-second order and Langmüir models, respectively. Infrared spectra show functional groups –OH, –NH, C-N, C-H, N-H, C=O, that play an essential role in the adsorption of Pb, Hg and Cd on fungal biomass.